PERFORMANCE OF WEANER RABBITS FED VARYING LEVELS OF SWEET POTATO MEAL AS DIETARY ENERGY SOURCE - Ibrahim, Z.; Bello, K.M.; Egbo, M.L.; Garba, S.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
This experiment was conducted at the Teaching and Research farm, College of Agriculture, Bauchi to study the performance, carcass and cost benefit of using 0, 20, 40 and 60% replacement levels of sweet potato meal for maize as energy sources in weaner rabbits diet. A total of twenty four (24) Mongrel rabbit weighing between 921.66 – 938.17g were randomly allocated to the four dietary treatments in replicates of three containing two rabbits each in Completely Randomized Design (CRD). Each replicate was served 100g of the diet and 500ml of water daily. The result of the performance indicated that Daily Feed Intake (DFI) showed a significant treatment effect and ranged from 40.31 to 44.43g on diets 3 and 1 respectively. The daily weight gain was between 4.35g in (diet 1) and 3.68 in (diet 2) and non-significantly different. Feed conversion ratio which was also not significantly affected, was between 9.67 in (diet 3) and 11.33 in (diet 2). All the carcass and organs characteristics of rabbits, shows a non significant treatment effect except the caecal weight. Feed cost/kg gain was lowest on diet 3 (N5167.74) and highest in diet 2 (N6123.75), while diet 3 (N412.74) had the highest cost saving. It can be concluded that sweet potato meal as dietary energy source can best replace maize at 40% level in the diets of weaner rabbits with compare the performance, carcass, organ characteristics and cost benefit. Diet containing 40% also had the highest cost benefit (N4127.74) and therefore recommended for rabbit production.